High-resolution global mature and young oil palm plantation subclass maps for 2020 - You Xu; Dongjie Fu; Hao Yu; Fenzhen Su; Vincent Lyne; Rong Fan; Bin He; Tingting Pan; Jiasheng Tang (International Journal of Digital Earth, 2023)
Accurate high-resolution maps of oil palm plantations underpin effective management of environmental and socio-economic impacts at global, regional, and national levels. However, young industrial and highly irregular small-holder plantations are mostly unmapped and not included in official FAO statistics. This issue is addressed here by discriminating global oil palm plantation in 2020 into four subclasses: Industrial Mature Oil Palm (IMOP); Industrial Young Oil Palm (IYOP); Smallholder Mature Oil Palm (SMOP); and Smallholder Young Oil Palm (SYOP). Data, resolved to 4.77 m, from Planet & NICFI, Sentinel-1/2, were combined with other layers using the image-oriented classification and regression tree (CART) algorithm which performed best in classification tests. Results show that SMOP dominates distributional extent, but it was also the most accurately mapped subclass typically found at 500–1000 m altitude. IMOP had the most extensive altitude range of 500–1300 m, while IYOP and SYOP were found at similar altitudes of 500–800 m and 500–900 m respectively. Recent developments in South East Asia show oil palm plantations expanding into new areas with a slope of 24 degrees. Results provide data to support Sustainable Development Goal by assisting future oil palm-related development planning and monitoring in the world's major oil palm-growing countries.